Information System Security Risk Assessment NIST SP 800-30 Framework Selector Data - zeckyan zeckyan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Information security is an action to protect information against various threats in order to ensure the continuity of business processes, as well as minimize or eliminate threat risks and maximize profits and business opportunities for an organization. Risk assessment is the steps for analyzing or describing risks, and provides strategies that can be implemented to minimize risks. Pekanbaru City General Election Commission (KPU) Office One of the companies or organizations that have implemented an information system but has not evaluated information security risks and there is no risk management, especially in the field of IT infrastructure. In this study the authors used the NIST SP 800-30 method to conduct risk research, this method is a method that provides various management guidelines and risk assessments in order to minimize the level of risk threats from United States government standards. The results of the assessment using the Information Security Risk Assessment System using the NIST SP 800-30 method against the Pekanbaru General Election Commission voter list system, obtained two (2) low level risks, two (2) medium level risks, two (2) high level risks.